Optimizing vaccine uptake in sub-Saharan Africa: a collaborative COVID-19 vaccination campaign in Madagascar using an adaptive approach - Viola Pavoncello; Irina Kislaya; Diavolana Koecher Andrianarimanana; Valentina Marchese; Rivo Rakotomalala; Tahinamandranto Rasamoelina; Simon Veilleux; Ariane Guth; Alexina Olivasoa Tsiky Zafinimampera; Sonya Ratefiarisoa; Olivette Totofotsy; Cheick Oumar Doumbia; et al. (Implementation Science)
Abstract Background The COVID-19 pandemic has highlighted the need for more effective immunization programs, including in limited resource settings. This paper presents outcomes and lessons learnt from a COVID-19 vaccination campaign (VC), which used a tailored adaptive strategy to optimise vaccine uptake in the Boeny region of Madagascar. Methods Guided by the Dynamic Sustainability Framework (DSF), the VC implementation was regularly reviewed through multi-sectoral stakeholder feedback, key informant interviews, problem-solving meetings, and weekly monitoring of outcome indicators to identify and apply key adaptations. Qualitative data on processes were collected and analysed using a rapid assessment approach. Outcome indicators, including pre- and post-VC vaccine hesitancy and trends in vaccine doses administered, were analysed using generalized linear models. Additionally, vaccination coverage, geographic reach, and target population characteristics, and sustainability indicators, such as staff trained, facilities equipped, and degree of integration of operational and educational materials were also tracked. Results Key strategy adaptations included using a proactive campaign approach, community-led awareness and outreach, particularly in remote areas, and addressing cold chain, waste management, vaccine transport, and information technology (IT) equipment gaps. Over six months, 24,888 COVID-19 vaccines were administered. The adapted strategy led to an 8% increase in doses administered weekly (RR = 1.08, CI 95%: 1.01-1.15). However, vaccine hesitancy among the unvaccinated population remained unchanged (∆ = 0.02, CI 95%: -0.04-0.08). In terms of sustainability, 340 staff were trained, and 10 primary healthcare facilities were equipped and refurbished. Conclusions Implementing collaborative, multi-sectoral vaccination strategies that integrate healthcare services with proactive outreach and community-driven campaigns are effective in increasing vaccine coverage in resource-limited settings. It demonstrates how theory-based adaptive strategies can enhance vaccination rates, even if they do not significantly impact COVID-19 vaccine hesitancy within the community. More generally, this initiative has important implications for adult vaccination programmes other than those related to COVID-19.